Renal histological heterogeneity and functional progress in normoalbuminuric and microalbuminuric Japanese patients with type 2 diabetes. Issue 1 (8th August 2014) - Moriya, Tatsumi; Suzuki, Yoshiki; Inomata, Shigeki; Iwano, Masayuki; Kanauchi, Masao; Haneda, Masakazu
Abstract : Background and objectives: Renal histological injury patterns in type 2 diabetes are heterogeneous. We compared renal histological injury patterns using renal biopsy findings with renal function and followed up renal functional changes in normoalbuminuric and microalbuminuric patients with type 2 diabetes to determine whether renal function progresses according to injury patterns. Design, setting, participants, and measurements: We examined 111 patients with type 2 diabetes with percutaneous renal biopsy (78 men, 52±11 years old, 59 normoalbuminuria, 52 microalbuminuria) and followed up 37 cases for 11 years. Light microscopy of tissues revealed renal injury patterns as: category I (CI), normal or near-normal structure; category II (CII), typical diabetic glomerulopathy; category III (CIII), atypical (disproportionately severe tubulointerstitial/vascular damage with no/mild glomerulopathy). Results: There were 29 CI, 62 CII, and 20 CIII patients. CII patients had a higher frequency of chronic kidney disease (CKD) G3-4, while the injury pattern distribution was not different among the albuminuria stages. The mean glomerular volume and volume fraction of cortical interstitium were larger than those of controls. The arteriolar hyalinosis index was larger in CII and CIII, while the percent global glomerular sclerosis was larger in CKD G3-4 compared with CKD G1-2. Renal function at follow-up was decreased in CII and CIII compared with the baseline estimated glomerular filtration rate (eGFR), while the GFR decline rate was faster in CII. Conclusions: In normoalbuminuric and microalbuminuric patients with type 2 diabetes, loss of GFR could indicate typical diabetic glomerulosclerosis and a high frequency of global glomerular sclerosis. Urinary biomarkers identifying histological patterns of renal injury are necessary because GFR decline rates differed according to histological injury patterns.